NetMetric: Uma Plataforma para Medição Ativa de Desempenho em Redes IP de Larga Escala - Lautenschläger , William; Costa Filho , Roberto; Kagami, Nicolas; Flora , Saymon Della; Moura , Karina de; Roesler, Valter (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
Network management is already an extensively investigated topic in academia, as well as implemented in countless commercial and Open Source solutions. However, the network management scene is rapidly becoming more complex, not only because of the growth of telecommunication networks, but also from the advent of new technologies such as Software Deﬁned Networks (SDN) and Network Function Virtualization (NFV)[6, 3]. In this context, service providers are faced with a challenge in the form of implementing large scale strategies for obtaining accurate measurements about the quality of the provided services. This paper describes the NetMetric tool, a solution which employs active measurement techniques to determine fundamental indicators of the IP network performance. This document presents the tool in its general architecture, its high scalability aspects, as well as a brief case study to depict operation.